Reliability of Capillary Blood Gas Measurements in Paralympic Sprinters at Rest: A Pilot Study - Thiago Fernando Lourenço; Samuel Bento da Silva; Vinícius Miguel Zanetti; Ana Gabriela Almeida Maximo Pereira; João Vitor Ichikawa Quintella; Oriane Martins; Amaury Verissimo; Lazaro Alessandro Soares Nunes (Sports, 2025)
Background: Sports scientists have increasingly used point-of-care methods for training load management, and blood gas analysis has shown promise in this area. However, the reproducibility of this method in high-performance athletes remains unproven. Objective: The aim of this study was to verify the reliability of acid-base variables at rest in high-performance Paralympic sprinters. Methods: Seven athletes participated, including four with visual impairments (class T12 and T13) and three with physical impairments. Approximately 500 µL of capillary blood was obtained from the fingertip and analyzed in triplicate (Samples 1, 2, and 3) using the Epoc System® (Ottawa, ON, Canada) to measure pH, carbonic dioxide partial pressure (pCO2), bicarbonate ion (HCO3−), base excess (BE), hematocrit (Hct), hemoglobin concentration (Hb), creatinine (CRE), and urea concentration (URE). Results: No differences were found for any parameter (p > 0.05). The imprecision of the method ranged from 0.1% for blood pH to 6.1% for BE. Pearson’s analysis showed strong and significant relationships between all variables analyzed (p < 0.05). The degree of consistency among samples also indicated excellent reliability of measurements, ranging from 0.88 for Hb to 1.00 for URE. Conclusions: These results indicate that acid-base status measurements using point-of-care demonstrated excellent reliability in high-level athletes, supporting sports scientists and coaches for athlete training and management.